Quorum Sensing and Biofilm Dynamics in Pathogens: An Evolving Frontier in Infectious Disease - Kulsum Jamal (International Journal of Pathogens, 2026)
Bacterial and fungal pathogens rarely act as solitary invaders. Instead, they engage in sophisticated chemical communication known as quorum sensing (QS) to coordinate population-wide behaviours and construct structured, multicellular biofilm communities. These biofilms, composed of extracellular polymeric substances, not only facilitate microbial persistence on biotic and abiotic surfaces but also confer remarkable protection against host immune defenses and antimicrobial therapies. QS systems act as central regulators of biofilm dynamics, orchestrating processes from initial attachment to maturation and dispersal, thereby enabling pathogens to adapt to fluctuating environments and colonize diverse niches. The interplay between QS and biofilm formation has profound clinical implications, particularly in chronic infections such as cystic fibrosis lung disease, endocarditis, and persistent device-related infections where conventional antimicrobial strategies often fail. Moreover, biofilm-mediated tolerance contributes significantly to the global antimicrobial resistance (AMR) crisis. This review explores the molecular mechanisms linking QS and biofilm development, providing illustrative case studies from clinically important bacteria (Pseudomonas aeruginosa, Staphylococcus aureus) and fungi (Candida albicans). It further examines the diagnostic and therapeutic challenges posed by QS-regulated biofilms, with emphasis on emerging strategies including quorum sensing inhibitors, matrix-degrading enzymes, engineered biomaterials, phage therapy, and host-directed interventions. Finally, we highlight key research gaps, evolutionary considerations, and translational hurdles that must be addressed to harness anti-QS and anti-biofilm strategies in clinical practice. Together, these insights position quorum sensing and biofilm biology as an evolving frontier in infectious disease management.
Keywords: Biofilm; Pseudomonas aeruginosa; Quorum sensing; antimicrobial resistance; chronic infections